Procedures of decoding in channels with errors and eliminations - Кубицкий, В. И. (Problems of Informatization and Control, 2007)
Proved, that for the correction of eliminations of multipleness of e and for a discovery and correction of errors of multipleness it is necessary the t code of Lagranzha and sufficiently 2t+e of characters of verifications. It is shown, as by the codes of Lagranzha it is possible to retrieve mistakes and eliminations. An algorithm consists in decoding of frequent errors after deletion of the effaced characters. A few methods of calculation of syndromes are examined at decoding of Lagranzha a code parcel errors and eliminations took place in which